Water Effect on Amine-Modification of Adsorbents for Separation of CO2/N2 - 张中正 汤娇娣 孙艳 苏伟 (Transactions of Tianjin University, 2013)
The adsorption of CO2 can be enhanced through loading amines on adsorbents, therefore, the separation of CO2 from other gases is promoted. Water plays an important role in this process. Water increases both the adsorption amount of CO2 and the separation coefficient with N2 for all amines loaded. However, the effect of loading trialkylamines is not remarkable in the absence of water. The effect of loading dialkylamine does not depend on water, but the adsorbent cannot be regenerated at ambient temperature. In comparison, an adsorbent loading trialkylamine can be regenerated at ambient temperature even in the presence of water with fairly good stability.